Functional evaluation of Desmostachya bipinnata-enhanced silver nanoparticles in mucoadhesive patches for enhanced oral drug delivery and tissue regeneration - Nitya Krishnasamy; Ramya Ramadoss (Next Materials)
A green-synthesized, ethanolic-based Desmostachya bipinnata-silver (Db-Ag) mucoadhesive patch was developed and comprehensively characterized for its physicochemical, mechanical, and biological properties. Scanning Electron Microscopy (SEM) revealed a crystalline morphology with nanoparticle sizes ranging from 20 to 30 nm, while Energy-Dispersive X-ray Spectroscopy (EDS) confirmed the presence of silver, oxygen, sodium, and chloride, validating the elemental composition. FTIR analysis identified functional groups such as –CH, –CO, –OH, and aliphatic –CH, suggesting the presence of phytoconstituents and bioactive compounds that enhance functionality. The patch demonstrated a tensile strength of 2.60 N and a contact angle of 66.28°, indicating favorable mechanical stability and moderate hydrophilicity suitable for mucosal adhesion. The in vitro drug release profile showed efficient and sustained release, supporting its potential for localized drug delivery in oral applications. Hemocompatibility assessment revealed less than 5 % hemolysis, confirming its biocompatibility, while significant hemostatic activity further reinforced its application in wound healing. The patch also exhibited broad-spectrum antimicrobial activity, with higher MIC values noted against Streptococcus mutans, Staphylococcus aureus, Escherichia coli, Candida albicans, and Enterococcus faecalis. Notably, anti-inflammatory activity reached up to 80 % in a dose-dependent manner, with an IC₅₀ value of 264.18 µg/mL. MTT assay against HeLa cells demonstrated dose-dependent anti-tumor efficacy across a concentration range of 25–400 µg/mL. In vivo testing with zebrafish indicated excellent regenerative activity. Furthermore, the patch exhibited high pH stability (99.4 % at pH 7) and sustained mechanical integrity under simulated mastication stress, highlighting its robustness and applicability for intraoral use.